Global Philosophy versus Colonial History of Philosophy: The Reconstruction of a non-Ethnocentric Philosophylogos as an Alternative to the “Western Culture Myth” - Herbjørnsrud, Dag (Nordlit, 2025)
This text shows how we have the opportunity to obtain a more balanced, scientific and non-ethnocentric presentation of the global history of philosophy. The text takes as its starting point how both the painter Raphael and other Renaissance thinkers give the Muslim-Arab European peer Ibn Rushd (Averroës) a central position in the history of philosophy, in contrast to how philosophy students today are introduced to philosophy and science as a “Greek invention”. As an alternative to today’s exclusionary Scandinavian representations of philosophy, reference is made to recent, international research where we have gained a wealth of new, accessible philosophical classics from Africa, Asia and America. In sum, an alternative to a “Western cultural myth” and a colonialist presentation of the history of philosophy is outlined: a decolonized logos based on a global philosophical perspective, starting from a context-based and comparative methodological approach.